Childhood Sjögren syndrome: Features of an international cohort and application of the 2016 ACR/EULAR classification criteria - Basiaga, Matthew L.; Stern, Sara M.; Mehta, Jay J.; Edens, Cuoghi; Randell, Rachel L.; Pomorska, Anna; Irga-Jaworska, Ninela; Ibarra, Maria F.; Bracaglia, Claudia; Nicolai, Rebecca; Susic, Gordana; Boneparth, Alexis; et al. (Oxford University Press (OUP), 2021)
Objective: Sjögren syndrome in children is a poorly understood autoimmune disease. We aimed to describe the clinical and diagnostic features of children diagnosed with Sjögren syndrome and explore how the 2016 ACR/EULAR classification criteria apply to this population. Methods: An international workgroup retrospectively collected cases of Sjögren syndrome diagnosed under 18 years of age from 23 centres across eight nations. We analysed patterns of symptoms, diagnostic workup, and applied the 2016 ACR/EULAR classification criteria. Results: We identified 300 children with Sjögren syndrome. The majority of patients n = 232 (77%) did not meet 2016 ACR/EULAR classification criteria, but n = 110 (37%) did not have sufficient testing done to even possibly achieve the score necessary to meet criteria. Even among those children with all criteria items tested, only 36% met criteria. The most common non-sicca symptoms were arthralgia [n = 161 (54%)] and parotitis [n = 140 (47%)] with parotitis inversely correlating with age. Conclusion: Sjögren syndrome in children can present at any age. Recurrent or persistent parotitis and arthralgias are common symptoms that should prompt clinicians to consider the possibility of Sjögren syndrome. The majority of children diagnosed with Sjögren syndromes did not meet 2016 ACR/EULAR classification criteria. Comprehensive diagnostic testing from the 2016 ACR/EULAR criteria are not universally performed. This may lead to under-recognition and emphasizes a need for further research including creation of paediatric-specific classification criteria.
Keywords: childhood Sjögren syndrome; pediatric rheumatology; recurrent parotitis; Sjögren Syndrome